2014
DOI: 10.1007/s10840-014-9940-9
|View full text |Cite
|
Sign up to set email alerts
|

Improved conduction and increased cell retention in healed MI using mesenchymal stem cells suspended in alginate hydrogel

Abstract: Introduction Mesenchymal stem cells (MSCs) have been associated with reduced arrhythmias; however, the mechanism of this action is unknown. In addition, limited retention and survival of MSCs can significantly reduce efficacy. We hypothesized that MSCs can improve impulse conduction and that alginate hydrogel will enhance retention of MSCs in a model of healed myocardial infarction (MI). Methods and results Four weeks after temporary occlusion of the left anterior descending artery (LAD), pigs (n=13) underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…Nevertheless, in those previous studies MSCs were co-cultured with normal cardiomyocytes, which may not be the actual clinical setting. For example, we have previously shown that when MSCs are infused at the time of injury arrhythmia vulnerability is decreased [49], and when MSCs are directly injected into borderzone tissue impulse conduction slowing is reduced [50]. Moreover, as suggested in the present study paracrine action may also lessen Ca ++ mediated arrhythmia substrates such as alternans, which are heightened in the infarct border zone [26, 51].…”
Section: Discussionsupporting
confidence: 53%
“…Nevertheless, in those previous studies MSCs were co-cultured with normal cardiomyocytes, which may not be the actual clinical setting. For example, we have previously shown that when MSCs are infused at the time of injury arrhythmia vulnerability is decreased [49], and when MSCs are directly injected into borderzone tissue impulse conduction slowing is reduced [50]. Moreover, as suggested in the present study paracrine action may also lessen Ca ++ mediated arrhythmia substrates such as alternans, which are heightened in the infarct border zone [26, 51].…”
Section: Discussionsupporting
confidence: 53%
“…We have found that administration of c-kit POS cardiac progenitors cells (CPCs) results in a sustained (up to 1 year) improvement in left ventricular (LV) function and structure despite the fact that almost all exogenous cells disappear within a few days of transplantation [6, 7, 14, 15, 19, 28, 30, 31, 33]. Similar findings have been reported by others with various cell types [14, 8, 13, 16, 17, 2325, 32, 36]. In view of the fact that transplanted cells are rapidly cleared from the myocardium, we posit that administration of one dose of cells cannot be regarded as a valid test of the therapeutic efficacy of that product.…”
Section: Introductionsupporting
confidence: 65%
“…Further studies have shown that the concentration of alginate, and thus mechanical stiffness, also plays a significant role in cell retention. MSCs transplanted in a 2% alginate solution (~2 kPa) were found to be retained and survive 4x higher than that of cells transplanted with saline or even 1% alginate (~700 Pa) [105]. …”
Section: Specific Hydrogel Design Choices For Specific Tissue Applmentioning
confidence: 99%